Negociação e hibridismo cultural no espaço missioneiro do Guairá pelos escritos de Antonio Ruiz de Montoya (1609-1632) - Soares, Washington Roberto Almeida (2012)
The work aims to analyze the civilizing process employed by the Jesuits in the missions of Guairá between the years 1609 and 1632, with reference to the central theoretical concept of cultural negociation, as conceived by Hommi Bhabha. According to our hypothesis, the introduction of the eurochristian culture among the Guarani took place through intense cultural negotiation between the parties involved. This movement inaugurated the construction of intersubjective bridges between the Indians and the religious, which therefore resulted in a hybrid culture, with aspects of both the Guarani and the Christian cultures, redefined in the missionary area, that will be treated as an in-between place. We will discuss the interpretation of the cultural practices of the Guarani, their appropriation and further representation of the Gentile Indian and the Reduced Indian. The sources that feed our approach include, in particular, the writings of Father Antonio Ruiz de Montoya, one of the pioneers of reductional experience in the region.